2016
DOI: 10.1088/1742-6596/708/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

The minimal channel: a fast and direct method for characterising roughness

Abstract: Abstract. Roughness only alters the near-wall region of turbulent flow and leaves the outerlayer unaffected, making it a prime candidate for the minimal-span channel framework which only captures the near-wall flow. Recently, Chung et al. (J. Fluid Mech., vol. 773, 2015, pp. 418-431) showed that the minimal-span channel can accurately characterise the hydraulic behaviour of roughness. Following on from this, we aim to further optimise the minimal-span channel framework by primarily noting that the outer laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…According to Lozano-Durán & Jiménez (2014), our computational domain is sufficiently large. It is worth noting that domains that are much smaller were used to study rough-wall boundary layer flows at moderate surface coverage densities (Chung et al 2015;MacDonald et al 2016MacDonald et al , 2017. Table 1 summarizes all the LES cases.…”
Section: Large-eddy Simulationsmentioning
confidence: 99%
“…According to Lozano-Durán & Jiménez (2014), our computational domain is sufficiently large. It is worth noting that domains that are much smaller were used to study rough-wall boundary layer flows at moderate surface coverage densities (Chung et al 2015;MacDonald et al 2016MacDonald et al , 2017. Table 1 summarizes all the LES cases.…”
Section: Large-eddy Simulationsmentioning
confidence: 99%
“…(2015) and MacDonald et al. (2016) employed the idea of DNS in minimal span channels (Jiménez & Moin 1991; Flores & Jiménez 2010) for prediction of roughness-induced drag over a regular sinusoidal roughness in a channel. The central idea followed by these authors is that the amount of downward shift in the inner-scaled velocity profile is the determining factor in the prediction of drag.…”
Section: Introductionmentioning
confidence: 99%
“…Standard DNS, however, involves resolving the entire spectrum of turbulent length scales ranging from large geometrical scales to the small viscous scale, which is computationally costly. To tackle this problem, Chung et al (2015) and MacDonald et al (2016) employed the idea of DNS in minimal span channels (Jiménez & Moin 1991;Flores & Jiménez 2010) for prediction of roughness-induced drag over a regular sinusoidal roughness in a channel. The central idea followed by these authors is that the amount of downward shift in the inner-scaled velocity profile ΔU + is the determining factor in the prediction of drag.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, all simulations are performed at Re τ = 800. Due to the high computational demand of many DNS, the concept of DNS in minimal channels (Chung et al 2015;MacDonald et al 2016) is adopted for the considered simulations. Recently, Yang et al (2022) showed the applicability of this concept for flow over irregular roughness subject to certain criteria.…”
Section: Direct Numerical Simulationsmentioning
confidence: 99%